2021
DOI: 10.1109/lemcpa.2021.3119256
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Time-Domain Analysis of Equipment in Low-Voltage Networks

Abstract: The increased use of non-linear equipment results in conducted electromagnetic interference problems. As an example, static energy meters, used to measure the energy consumption in households, show misreadings due to pulsed currents from a speed controlled water pump or dimmed lighting equipment. To determine the existence of similar equipment in low-voltage networks, this letter surveys current waveforms drawn by equipment in the low-voltage network. These waveforms are analyzed and compared to critical wavef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Using two on-site studies it was found that those interfering waveforms are representative for the actual residential grid. First, an extensive study on the waveforms from individual appliances that are typically connected in a residential grid showed that 43% of the surveyed equipment has parameters inside the critical range related to the static energy meter interference [15]. Second, the waveforms that occur at the meter connection point are surveyed in [16] at representative sites including modern sites that include an electric vehicle (EV) charging station and a photovoltaic (PV) installation.…”
Section: A Interference Waveformsmentioning
confidence: 99%
“…Using two on-site studies it was found that those interfering waveforms are representative for the actual residential grid. First, an extensive study on the waveforms from individual appliances that are typically connected in a residential grid showed that 43% of the surveyed equipment has parameters inside the critical range related to the static energy meter interference [15]. Second, the waveforms that occur at the meter connection point are surveyed in [16] at representative sites including modern sites that include an electric vehicle (EV) charging station and a photovoltaic (PV) installation.…”
Section: A Interference Waveformsmentioning
confidence: 99%
“…To assess the underlying problem of the SM misreadings, this chapter describes a measurement technique for characterizing the currents that SMs are usually exposed to. The work presented incorporates the research published in [34], [77]- [80].…”
Section: Waveform Characterizationmentioning
confidence: 99%